Control of Listeria monocytogenes in an avocado processing facility - Strydom, Amy (University of the Free State, 2015)
Listeria monocytogenes contamination of food is a growing concern for the food industry since it is the causative agent of human listeriosis. Despite increased awareness and strict microbiological standards for this pathogen, countries such as France, Austria and Germany have reported increases in listeriosis outbreaks. The research in this thesis shows how Listeria contamination in a South African avocado processing was almost eradicated. The first aim of this project was to isolate and genetically type the L. monocytogenes strains isolated from the facility. Pulsed field gel electrophoresis (PFGE) was used to group a subset of strains (n=80) according to the digestion of their genomes with the restriction enzyme AluI. These results were compared to polymerase chain reaction (PCR)-restriction fragment length polymorphism (RFLP) of the inlA gene (n=140). The results of the two methods compared well with each other but both indicated a lower genetic diversity among the isolates than expected. These strains were isolated over a period of four years and only two major groups were identified with the PFGE and the PCR-RFLP resulted in only three banding patterns. Also, the origin of the bacterial contamination could not be identified, but results indicated that cross contamination played a role in the persistence of these bacteria in this food processing facility. Secondly, the commercial product ListexTM P100 was assessed for possible use as a biocontrol agent in the facility. The host range of the phage product was determined based on 239 L. monocytogenes strains isolated from this facility, but only 26.7% of these strains were susceptible to the bacteriophage. The strains were also analysed for serotype and no correlation was observed between typing methods or isolation source and date of isolation of the strains, as well as the susceptibility to the phage product. This could indicate that cross contamination played a role in the transfer of bacterial cells since these strains were distributed randomly in the facility. Inoculation of the phage product with L. monocytogenes T162 in brain heart infusion (BHI) broth resulted in significant reductions in the bacterial concentration. However, activity of the phage in avocado pulp and guacamole was very low and no significant reduction in the L. monocytogenes concentration was measured. Lastly, the population of the Listeria strains in the facility were continuously monitored over five years. The final products and processing environment, including floors, equipment, work areas and personnel were tested on-site for Listeria with the ISO 11290-1 method. Based on the prevalence of Listeria, the facility introduced new strategies in processing to counter cross contamination. Results from the 2014 guacamole production season showed almost complete eradication of Listeria spp. in final products (0.17%, n=1170) and the processing facility (0.79%, n=1520). These results indicate that successful management of Listeria spp. in an avocado processing facility can be accomplished with in-house monitoring of the bacterial population and subsequent adjustments to the processing system. The results from this project indicated that the cause of contamination by L. monocytogenes in the facility was due to cross contamination, although a strict quality control system was followed. Despite low genetic variability between the L. monocytogenes strains, the commercial phage product was only effective against 26.7% of strains tested. This is surprising since literature reported very high percentages of susceptible strains to this specific product. Although bacteriophage biocontrol with ListexTM P100 was not effective in this facility, it cannot be concluded that this will be the case for other facilities. Also, bacteriophage product with a broader host range such as a cocktail of different phages, may work well in the processing environment to minimise transfer of bacterial cells to the final product. Control of L. monocytogenes will, however, only be effective if the processing conditions counter cross contamination.
Keywords: Listeriosis; Communicable diseases; Listeria monocytogenes; Food -- Microbiology; Thesis (Ph.D. (Microbial, Biochemical and Food Biotechnology))--University Free State, 2015